KnowLIT – Uma Ferramenta para apoio as atividades de Gestão do Conhecimento - Becker, Leandro Gustavo Biss; Renaux, Douglas P. B.; Strauhs, Faimara do Rocio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2002: Anais do XVI Simpósio Brasileiro de Engenharia de Software, 2002)
In this paper a tool named KnowLIT is presented. This tool provides support for several activities related to Knowledge Management: one can build a Knowledge Map that presents the Knowledge areas of a group or company; a number of attributes are available for each Knowledge area (links to documents, lists of persons working in that area, knowledge level of these persons,...); and the turnover can be managed by planning the number of people being trained in each area before an expert leaves the company.